2010
DOI: 10.1093/jnci/djq414
|View full text |Cite
|
Sign up to set email alerts
|

Independent Association of Lobular Involution and Mammographic Breast Density With Breast Cancer Risk

Abstract: BackgroundLobular involution, or age-related atrophy of breast lobules, is inversely associated with breast cancer risk, and mammographic breast density (MBD) is positively associated with breast cancer risk.MethodsTo evaluate whether lobular involution and MBD are independently associated with breast cancer risk in women with benign breast disease, we performed a nested cohort study among women (n = 2666) with benign breast disease diagnosed at Mayo Clinic between January 1, 1985, and December 31, 1991 and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
67
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(73 citation statements)
references
References 37 publications
5
67
1
Order By: Relevance
“…After adjusting for absolute nondense area, every additional 10 cm 2 of dense tissue was associated with a 7% increase in odds of breast cancer in all women (n 5 292, actual age range [40][41][42][43][44][45][46][47][48][49][50], but with a 14% increase in premenopausal women (n 5 200, actual age range [40][41][42][43][44][45][46][47][48][49][50]. MD may therefore be an even more important risk factor in premenopausal compared to postmenopausal women among those at higher-thanaverage risk not currently within screening age range.…”
Section: Discussionmentioning
confidence: 99%
“…After adjusting for absolute nondense area, every additional 10 cm 2 of dense tissue was associated with a 7% increase in odds of breast cancer in all women (n 5 292, actual age range [40][41][42][43][44][45][46][47][48][49][50], but with a 14% increase in premenopausal women (n 5 200, actual age range [40][41][42][43][44][45][46][47][48][49][50]. MD may therefore be an even more important risk factor in premenopausal compared to postmenopausal women among those at higher-thanaverage risk not currently within screening age range.…”
Section: Discussionmentioning
confidence: 99%
“…In support of this hypothesis, Ghosh et al reported an inverse association between mammographic density (defined by Wolfe's parenchymal patterns) and lobular involution among 2,667 women in the Mayo benign breast disease (BBD) cohort [5]. Compared with those with complete involution, women with no involution had an OR of 1.7 (95 % CI 1.2-2.3) of high density (DY pattern).…”
Section: Mammographic Density and Lobular Involutionmentioning
confidence: 95%
“…Involution was not, however, associated with the absolute dense area, but rather strongly positively associated with the absolute nondense area. Intriguingly, in a follow-up study based on the Mayo BBD cohort, Ghosh et al found that mammographic density and lobular involution are independent risk factors for breast cancer [5], arguing against the hypothesis that the association between mammographic density and breast cancer risk is explained to any large degree by involution. Ghosh et al also found that women with dense breasts and no lobular involution had the highest breast cancer risk and speculated that the stromal-rich environment in dense breasts results in a preponderance of growth factors that stimulate the epithelium in a non-involuted breast, which could lead to malignant transformation.…”
Section: Mammographic Density and Lobular Involutionmentioning
confidence: 99%
“…Clinical studies show that completion of lobular involution may reduce future breast cancer incidence [163][164][165][166]. With aging, there is a gradual loss of breast epithelial tissue that typically begins in peri-menopause, which then accelerates during menopause.…”
Section: Ems Receptormentioning
confidence: 99%
“…Lobular involution, like post-lactational involution, may inversely correlate with breast cancer risk, since premenopausal women who underwent partial or complete lobular involution had a substantially decreased incidence of breast cancer, while postmenopausal women who showed delayed lobular involution were found to have a correspondingly elevated breast cancer incidence [164]. While much remains to be learned about how lobular involution is regulated, some clinical studies and animal models suggest that IGF-1 may inhibit involution of lobules in the breast [163].…”
Section: Ems Receptormentioning
confidence: 99%